Functioning and productivity of Jan Aushadhi stores in India: The owners' perspective - Prasanna R Deshpande; Mohd Kazim Sheriff; Atmaram P Pawar (Wolters Kluwer Medknow Publications, 2018)
Objective: Jan Aushadhi (People's Medicine) Stores (JAS) are still struggling to get well established in India. Although the Jan Aushadhi (JA) scheme was launched in 2008, the number of JAS has not increased much until now. Therefore, we aimed to determine the working and productivity of JAS in the country. Methodology: We conducted a web-based survey of current JAS owners using a validated questionnaire. The questionnaire was sent to the E-mail addresses as mentioned on JA website. We solicited the information about the aspects such as background information, working and productivity of the store, hurdles while running a JAS, and the opinions. Results: One hundred and sixty-nine individuals responded to the survey out of 1008 (response rate = 16.76%). One hundred and forty-three (84.62%) JAS owners have reported the net monthly profit to be Rs. <5000/-. They have also reported that there are certain hurdles while running the shop. Other important average values for certain parameters were follows: patients approaching a JAS/day - 47.43, net profit/month - Rs. 4230.85, and prescriptions filled/day - 27.06. Conclusion: Dealing with generic drugs is a multifaceted and complex issue in India. JAS were not as "economically productive" as to a regular "government"/community pharmacy in India. There are some flaws as far as the functioning JAS is considered. Although JA scheme was launched long back, it has not spread well in the country until now. Productive inputs are essential for better running of the scheme. The government should think of the hurdles and the suggestions as reported by the JAS owners.